Janševe in Pahorjeve prepričevalne strategije na zadnjih parlamentarnih volitvah - Krajnc Ivič, Mira (Slavistična revija, 2011)
The author analyzes the strategies of voter persuasion employed by Janez Janša and Borut Pahor in their campaign speeches during the 2008 Slovenian general elections. She collected, transcribed, and analyzed from the linguistic point of view some of their campaign speeches or their parts. It appears that differences in the persuasive strategies in these speeches to some extent depend on the political party each politician represents and also on their personality. Janša persuades voters with inferences, poise, and personality, while Pahor, on the other hand, largely by playing on their emotions, with personality, and poise.
Keywords: discourse; državnozborske volitve; election speeches; general election; political linguistics; politično jezikoslovje; predvolilni govori; Slovene; Slovene language; slovenščina